2000
DOI: 10.1104/pp.123.1.81
|View full text |Cite
|
Sign up to set email alerts
|

Response to Xanthomonas campestris pv.vesicatoria in Tomato Involves Regulation of Ethylene Receptor Gene Expression

Abstract: Although ethylene regulates a wide range of defense-related genes, its role in plant defense varies greatly among different plant-microbe interactions. We compared ethylene's role in plant response to virulent and avirulent strains of Xanthomonas campestris pv. vesicatoria in tomato (Lycopersicon esculentum Mill.). The ethylene-insensitive Never ripe (Nr) mutant displays increased tolerance to the virulent strain, while maintaining resistance to the avirulent strain. Expression of the ethylene receptor genes N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
111
0
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 204 publications
(125 citation statements)
references
References 58 publications
13
111
0
1
Order By: Relevance
“…ETR4 is upregulated by Xcv and ethylene and negatively regulates tissue degeneration triggered by high ethylene levels (Ciardi et al, 2000). By contrast, ETR2 mRNA levels are not affected by Xcv or ethylene treatment.…”
Section: Xopd Suppresses Chlorophyll Loss and Alters Senescence-and Dmentioning
confidence: 96%
“…ETR4 is upregulated by Xcv and ethylene and negatively regulates tissue degeneration triggered by high ethylene levels (Ciardi et al, 2000). By contrast, ETR2 mRNA levels are not affected by Xcv or ethylene treatment.…”
Section: Xopd Suppresses Chlorophyll Loss and Alters Senescence-and Dmentioning
confidence: 96%
“…The present results that overexpression of the ethylene receptor gene NTHK1 led to reduced ethylene sensitivity may be consistent with previous reports. Ciardi et al (2000) found that tomato ethylene receptor NR overexpression reduced ethylene sensitivity in seedlings and mature plants. Consistently, transgenic plants with reduced LeETR4 gene expression displayed multiple symptoms of extreme ethylene sensitivity .…”
Section: Discussionmentioning
confidence: 99%
“…Homozygous lines of the NR overexpressing lines described earlier (25) were crossed to LeETR4 antisense lines LeETR4AS-1 (homozygous for the transgene) or LeETR4AS-2 (heterozygous for the transgene).…”
Section: Methodsmentioning
confidence: 99%
“…RNA was extracted with SDS͞phenol followed by LiCl precipitations (25). RNase protection assays were performed by using a manufacturer's kit (Ambion, Austin, TX) as described (17,18).…”
Section: Methodsmentioning
confidence: 99%